2022
DOI: 10.21203/rs.3.rs-1229969/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Testing the Effectiveness of a Future Selves Intervention for Increasing Retirement Saving: Evidence from a Field Experiment in Mexico

Abstract: One psychological barrier impeding saving behavior is the inability to fully empathize with one’s future self. Future self interventions have improved savings by helping people overcome this obstacle. Despite the promise of such interventions, previous research has focused predominantly on hypothetical contexts and western settings where the target sample has been predominantly undergraduate. Do interventions that encourage people to more concretely consider their future selves during retirement still have a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Field trials support this mechanism, showing that encouraging workers to consider their future-self can increase pension contribution rates (Bryan & Hershfield, 2013;Shah, Hershfield, Munguia Gomez & Fishbane, 2022).…”
Section: Inattentionmentioning
confidence: 93%
See 2 more Smart Citations
“…Field trials support this mechanism, showing that encouraging workers to consider their future-self can increase pension contribution rates (Bryan & Hershfield, 2013;Shah, Hershfield, Munguia Gomez & Fishbane, 2022).…”
Section: Inattentionmentioning
confidence: 93%
“…As outlined in Section 1.1, few studies have aimed to motivate saving. Two exceptions are recent tests of (1) reducing the psychological distance between the consumer's current and future self on saving for retirement (Shah et al, 2022) and (2) a social norm nudge to encourage saving (Dur et al, 2021). We did not seek to test these treatments.…”
Section: Communication Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on mental simulation has, for example, demonstrated that simulating future events can make them seem more vivid, fluent, and prominent (Kappes & Morewedge, 2016; Mrkva, Travers, & Van Boven, 2018). Mentally simulating the distant future can increase how much people prioritize saving for retirement (Hershfield, John, & Reiff, 2018) and other long-term goals (Rutchick, Slepian, Reyes, Pleskus, & Hershfield, 2018; Shah, Hershfield, Gomez, & Fertig, 2018). Mentally simulating risks can make them seem more severe and more likely to occur, especially if the risks are easy to imagine (Gregory, Cialdini, & Carpenter, 1982; Mevissen, Meertens, Ruiter, Feenstra, & Schaalma, 2009; Sherman, Cialdini, Schwartzman, & Reynolds, 1985).…”
mentioning
confidence: 99%